An optimization of composite sandwich structure with passive vibration absorber for vibration suppression. (November 2021) - Kim, Yongha; Park, Jungsun
This article proposes the use of a support as a passive vibration absorber to a composite sandwich structure for vibration suppression of satellite structures. Based on continuous mass distributions, an approximate formulation is presented for conducting vibration (modal, frequency response) analyses of the composite sandwich structure with the support. This formulation is derived by the Ritz method; verified for accuracy and computational efficiency by comparing finite element analyses. Finally, we perform optimization of the composite sandwich structure with passive vibration absorber by the present method. This optimization is conducted to applying satellite structures for maximizing vibration suppression performance in limited mass. The optimization result allows a database to be obtained on the vibration characteristics of composite sandwich structures with passive vibration absorber for applying aerospace applications. Consequently, it is concluded that the approximate formulation is well suited to vibration analyses of composite sandwich structures with passive vibration absorber due to their relative simplicity and computational efficiency.